Modelling and Optimization of An Integrated Steam Hub Facility for Brownfield Eco-Industrial Parks - Siti Nor Azreen Ahmad Termizi; Sharifah Rafidah Wan Alwi; Zainuddin Abdul Manan; Fakhrony Sholahudin Rahman; Petar Sabev Varbanov (Chemical Engineering Transactions)
Eco-Industrial Parks are vital for sustainable development and combating climate change by improving resource efficiency and adopting circular economy practices. Integration of common infrastructure like steam power plants and reutilizing resources collectively are among the crucial steps to achieve these objectives. This study focuses on modeling and optimizing the integration of existing steam utility plants into an integrated steam hub facility through Linear Programming (LP) approach. The optimization goal aims to minimize cost and emission reduction while ensuring a reliable energy supply for industrial operation. The finding demonstrates significant reductions in both cost and emissions. In the scenario involving only fossil fuel-based utility plants, the costs decreased by 2.78 % from 9,544.30 $/h to 9,278.74 $/h, and GHG emissions dropped by 11.8 % from 0.85 t/h to 0.75 t/h. Further integration with a renewable energy-based utility plant reduced GHG emissions by 16.5 % to 0.71 t/h, though with a slight increase in cost to 9,577.66 $/h. Furthermore, this integration strategy allows for the maximization of capital investment for stakeholders while providing a sustainable energy supply and opportunities to transition to greener energy sources through optimized resource utilization.